ANALISIS PENGARUH PENURUNAN TEMPERATUR PADA PROSES TUANG CAIRAN LOGAM DENGAN COVER LADLE DI PT. X - Faizal, Mohamad; Gunawan, Hendra (Bina Teknika, 2019)
Block Cylinder is an important component of a vehicle engine where the quality of the component should not be defect because it can affect the function of the vehicle engine. Block cylinder is made from cast iron material (FC 230) which must be melted with temperature >1400 ° C. The temperature of cast iron molten metal into the mold is a very important factor to guarantee final quality of block cylinder. Process pouring of molten metal into a mold using a ladle to pouring 15 molds. Pin hole defects often occur in the final castings, this is due to molten metal temperature drop at the end, the one factor is air convection suction smoke collector. Smoke collector is required to move the gas that arises during the pouring process to outside the factory in order to make a comfortable and healthy work process, but it has side effect speed up decreasing temperature of molten metal. To solve the decrease temperature is minimize the rate of heat transfer that occurs from molten metal to environmental air. One way is to close the ladle with the cover to reduce the heat transfer that occurs in the metal liquid. The material used as a ladle cover is Kaowooltm SZr, where it has low thermal conductivity and light density. The rate of heat transfer occurring in the metal liquid to the surrounding air without cover is 4,5563 kW. After using the ladle cover the rate of heat transfer from metal liquid to air decreases to 1.8287 kW. Then the liquid temperature of the final cast metal rises from 1369 ° C to 1383 ° C, and the pin hole defect occurring in the final cast decreases from 0.22% to 0.12%.